Digital Transformation and Customer Growth in Islamic Microfinance - Suryanti, Rufita Laily; Hidayatullah, M.F. (Yayasan Riset dan Pengembangan Intelektual, 2026)
Digital transformation has become a key strategy for Islamic financial institutions to improve service efficiency, expand reach, and facilitate transaction access for customers. BMT UGT Nusantara Umbulsari Branch, as an Islamic microfinance institution, has also begun implementing digital services through the Mobile UGT application. Although the use of digital services has shown an increase year over year, the level of utilization by customers is still not optimal. This situation indicates a gap between the availability of technology and user adoption. This study aims to examine the digital transformation process at BMT UGT Nusantara Umbulsari Branch, to identify the factors supporting the success of digital transformation at BMT UGT Nusantara Umbulsari Branch, and to assess the impact of digital transformation on increasing the number of customers at BMT UGT Nusantara Umbulsari Branch. The research approach employed is a qualitative approach. The research results indicate that the digital transformation process at BMT UGT Nusantara Umbulsari Branch was carried out in stages through digital strategy planning, the development of technological infrastructure and the Mobile UGT application, outreach to customers, as well as the implementation and optimization of digital services. The success of this digital transformation was supported by several key factors, namely management commitment, technological infrastructure readiness, human resource competence, and outreach and education strategies for customers. Furthermore, digital transformation has had a positive impact on customer growth, as evidenced by an increase in the number of customers, expansion of user segments, higher transaction frequency, and increased fund mobilization and service reach of the BMT.